Effects of the Transfer of Business in the Labor Relationship. Beyond the Application of the Principle of Continuity - Medina Valenzuela, Ingrid (2016)
In the last stage of development of capitalism, transfers of businesses are frequent. For this purpose, legal systems have regulated procedures to protect creditors and shareholders. In Peruvian legal system, the General Law of Corporations regulates these kinds of transfers through mergers, divisions and reorganizations. However, those operations influence in employment relationships because of the translation of its productive organizations. Even though, there is no regulation to determine the consequences of transfer in these kinds of relations in an organizational way, this legal gap is tend to be solved through the application of the principle of continuity developed by Peruvian jurisprudence.In this short paper, it defines the concept, elements, and the effects of the transfer of an undertaking from the perspective of labor law, giving special attention to the analysis of what the author calls “collateral “ or unwanted effects transfer , as aspects that go beyond the principle of continuity to safeguard labor rights.